Ablation of capsaicin sensitive afferent nerves impairs defence but not rapid repair of rat gastric mucosa. Issue 7 (July 1993) - Pabst, M A; Schöninkle, E; Holzer, P
Abstract : Capsaicin sensitive afferent neurones have previously been reported to play a part in gastric mucosal protection. The aim of this study was to investigate whether these nociceptive neurones strengthen mucosal defence against injury or promote rapid repair of the damaged mucosa, or both. This hypothesis was examined in anaesthetised rats whose stomachs were perfused with ethanol (25 or 50% in saline, wt/wt) for 30 minutes. The gastric mucosa was inspected 0 and 180 minutes after ethanol had been given at the macroscopic, light, and scanning electron microscopic level. Rapid repair of the ethanol injured gastric mucosa (reduction of deep injury, partial re-epithelialisation of the denuded surface) took place in rats anaesthetised with phenobarbital, but not in those anaesthetised with urethane. Afferent nerve ablation as a result of treating rats with a neurotoxic dose of capsaicin before the experiment significantly aggravated ethanol induced damage as shown by an increase in the area and depth of mucosal erosions. Rapid repair of the injured mucosa, however, as seen in rats anesthetised with phenobarbital 180 minutes after ethanol was given, was similar in capsaicin and vehicle pretreated animals. Ablation of capsaicin sensitive afferent neurones was verified by a depletion of calcitonin gene related peptide from the gastric corpus wall. These findings indicate that nociceptive neurones control mechanisms of defence against acute injury but are not required for rapid repair of injured mucosa.